2021
DOI: 10.3332/ecancer.2021.1317
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-pathological relationship between androgen receptor and tumour infiltrating lymphocytes in triple negative breast cancer

Abstract: Background Triple negative breast cancer (TNBC) is an aggressive subtype of breast cancer (BC) with ill-defined therapeutic targets. Androgen receptor (AR) and tumour-infiltrating lymphocytes (TILs) had a prognostic and predictive value in TNBC. The relationship between AR, TILs and clinical behaviour is still not fully understood. Methods Thirty-six TNBC patients were evaluated for AR (positive if ≥1% expression), CD3, CD4, CD8 and CD20 by immunohistochemistry. Stromal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…It is indeed expressed in breast cancer and several other tumor cell lines. Future work will collect normal breast tissue and breast cancer specimens, take fluorescence quantitative PCR and other methods to detect the relative expression of the gene in breast cancer and normal tissues, and design a well-thought-out experiment to explore the structure and function of the gene in depth [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is indeed expressed in breast cancer and several other tumor cell lines. Future work will collect normal breast tissue and breast cancer specimens, take fluorescence quantitative PCR and other methods to detect the relative expression of the gene in breast cancer and normal tissues, and design a well-thought-out experiment to explore the structure and function of the gene in depth [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…This tendency is detected in ERα-positive cases but not in ERα-negative cases ( van Rooijen et al 2018 ). Conversely, in TNBC breast cancers, a significant positive correlation between AR and CD3-positive T cell infiltration was observed ( Elghazawy et al 2021 ). These findings suggest that androgens have opposite effects on intratumoral T cell infiltration in ERα-positive and ERα-negative breast cancers.…”
Section: Androgen Action In Breast Cancer Stromal Cellsmentioning
confidence: 99%
“…As a result, the discovery of innovative TNBC therapeutics is critical. Recently, numerous investigations have revealed that additional types of hormone receptors, such as the androgen receptor, are expressed in TNBC (Gerratana et al, 2018;Traina et al, 2018;Elghazawy et al, 2021;Sridhar et al, 2022).…”
Section: Introductionmentioning
confidence: 99%